Implementation of Food Safety Traceability Systems in The Product Supply Chain at PT. XYZUsing Quality Function Deployment (QFD) - Khumairo, Syafrilla Dinda; Wahyuni, Hana Catur (UNIPA PRESS, 2021)
PT. XYZ is a food manufacturing company withshrimp crackers as its main product. Thisresearch aims to analyze and make improvementsto the food safety traceability system that hasbeen applied previously and to develop productsof PT. XYZ using Quality Function DeploymentMethod (QFD). This research uses paper-basedtraceability and Quality Function DeploymentMethod (QFD).After analyzing the food safetytraceability system and analyzing consumerneeds using the QFD method, the results of theanalysis show that the food safety traceabilitysystem is improved by integrating coding alongthe supply chain and improving documentation.Improvements using QFD method is based onthree main priorities, those are maintainingconsistency in the aspect of packaging accordingto prevailing standards, packaging product that isinformative, as well as maintaining andimproving the aspects of color, taste, and smell ofthe product.